Kadar Protein dan Daya Terima Mi Padat Gizi Berbasis Pangan Lokal Sebagai Alternatif Pangan Darurat - Irma Eva Yani; Marni Handayani; Hafifahtul Husna (Jurnal Sehat Mandiri, 2022)
Noodles are foods that adults and children like, there are various types of noodles, one of which is wet noodles. Wet noodles are high in carbohydrates, but low in protein, so you need to add protein from other foods such as dried rebon shrimp . The purpose of the study was to determine the protein content and acceptability of wet noodles substituting dry rebon shrimp flour. This type of research is experimental research in the field of food technology with complete randomized design (RAL) one control, three treatments, two repetitions. Test protein levels in the laboratory Baristand Padang and receptivity Test at SDN 10 Surau Gadang. The study was conducted from March 2020 to April 2021. Organoleptic test results obtained the best treatment with a ratio of 75: 25 grams, 8.1% protein content with an increase of 3.5% protein, 80% target can spend product means wet noodles is acceptable. It is suggested that in the production process of wet noodles should use a substitution of dry rebon shrimp flour as much as 25 grams, and further research to test the shelf life and food safety.